Theopneustia the plenary inspiration of the Holy Scriptures - Gaussen, L. 1790-1863; Scott, David D.; Carr, B.W. (London, UK Chas. J. Thunne, 1912)
Includes bibliographical references
Keywords: Bible -- inspiration